Analogs of 6-Bromohypaphorine with Increased Agonist Potency for α7 Nicotinic Receptor as Anti-Inflammatory Analgesic Agents - Igor A. Ivanov; Andrei E. Siniavin; Victor A. Palikov; Dmitry A. Senko; Irina V. Shelukhina; Lyubov A. Epifanova; Lucy O. Ojomoko; Svetlana Y. Belukhina; Nikita A. Prokopev; Mariia A. Landau; Yulia A. Palikova; Vitaly A. Kazakov; et al. (Marine Drugs, 2023)
Hypaphorines, tryptophan derivatives, have anti-inflammatory activity, but their mechanism of action was largely unknown. Marine alkaloid L-6-bromohypaphorine with EC50 of 80 μM acts as an agonist of α7 nicotinic acetylcholine receptor (nAChR) involved in anti-inflammatory regulation. We designed the 6-substituted hypaphorine analogs with increased potency using virtual screening of their binding to the α7 nAChR molecular model. Fourteen designed analogs were synthesized and tested in vitro by calcium fluorescence assay on the α7 nAChR expressed in neuro 2a cells, methoxy ester of D-6-iodohypaphorine (6ID) showing the highest potency (EC50 610 nM), being almost inactive toward α9α10 nAChR. The macrophages cytometry revealed an anti-inflammatory activity, decreasing the expression of TLR4 and increasing CD86, similarly to the action of PNU282987, a selective α7 nAChR agonist. 6ID administration in doses 0.1 and 0.5 mg/kg decreased carrageenan-induced allodynia and hyperalgesia in rodents, in accord with its anti-inflammatory action. Methoxy ester of D-6-nitrohypaphorine demonstrated anti-oedemic and analgesic effects in arthritis rat model at i.p. doses 0.05–0.26 mg/kg. Tested compounds showed excellent tolerability with no acute in vivo toxicity in dosages up to 100 mg/kg i.p. Thus, combining molecular modelling and natural product-inspired drug design improved the desired activity of the chosen nAChR ligand.